The unanimity rule and corporate tax revenue in the EU - Martin Beznoska; Tobias Hentze (Institut der deutschen Wirtschaft (IW), 2019)
Politicians accuse corporations of sneakily shifting their profits to tax havens. In fact, tax revenues in low-tax countries such as Ireland and Malta have risen sharply over the past 20 years. However, revenue growth in large countries like Germany and France is not slow. Interestingly, EU countries which favor the unanimity rule in tax issues show higher growth rates in tax revenue than countries preferring a qualified majority system.
Keywords: 330